Catheter ablation of atrial fibrillation in patients with heart failure and preserved ejection fraction: A meta‐analysis. Issue 7 (11th May 2022) - Gu, Gaoyang; Wu, Jing; Gao, Xiaofei; Liu, Meijun; Jin, Chaolun; Xu, Yizhou
Abstract: Background: Catheter ablation (CA) is an effective treatment for patients with atrial fibrillation (AF). The potential of CA to benefit AF patients with heart failure and preserved ejection fraction (HFpEF) is uncertain. Hypothesis: CA may be safe and effective for patients with HFpEF. Methods: The Medline, PubMed, Embase, and Cochrane Library databases were searched for studies evaluating CA for AF patients with HFpEF. Results: A total of seven trials with 1696 patients were included. Pooled analyses demonstrated similar procedure and fluoroscopy time regarding the use of CA for patients with HFpEF and without HF (weighted mean difference [WMD]: 0.40; 95% confidence interval (CI): −0.01–0.81, p  = .05 and [WMD: 0.05; 95% CI: −0.18–0.28, p  = .68]). Moreover, CA was effective in maintaining sinus rhythm (SR) in patients with HFpEF and noninferior for patients without HF [risk ratio (RR): 0.92; 95% CI: 0.76–1.10, p  = .34). Additionally, CA tended to significantly maintain SR (RR: 4.73; 95% CI: 1.86–12.03, p  = .001) and reduce rehospitalization for HF compared with medical therapy (RR: 0.36; 95% CI: 0.19–0.71, p  = .003). However, no significant differences were found between two groups regarding the mortality rate ( p  = .59). Conclusion: CA is a potential treatment strategy for patients with HFpEF and demonstrates equivalent efficacy to that of patients without HF. Moreover, the benefits of CA in maintaining SR and reducing rehospitalization of HF patients were significantly better than those of medical therapy. Additional randomized controlled trials are warranted to confirm our results.